LGBT DALAM PERSPEKTIF HAM DAN MENURUT UUDN 1945 - Muzakkir Muzakkir (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2021)
This study aims to find out and explain how Indonesian people respond to LGBT behavior practices, how is the concept of Fulfillment of Human Rights in Indonesia for every citizen, how is human rights adopted and in accordance with the context to Indonesia ?, In this study, the author uses an approach case (case approach) and supplemented with literature review. This research is descriptive analytic, which is a method of collecting data and then analyzed using cases, coupled with reference books, legislation, and internet sources to support research. The results showed that the Indonesian people recognized the existence of LGBT that developed in other countries, including its presence in Indonesia, but Indonesian people who were based on religious values and values that lived and developed society could not accept LGBT behavioral practices. Fulfillment of the rights of every citizen does not necessarily without restrictions, including in terms of LGBT practice behavior, the state can provide restrictions in accordance with what has been stipulated in the law, which contains values that live in society. Human rights adopted by Indonesian citizens are limited (particular) not infinite (universal) as has been practiced by western countries.